2001
DOI: 10.1103/physrevb.63.064404
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phase separation on the magnetization, x-ray diffraction, and Raman scattering of(La1yNdy

Abstract: Dc-magnetization, x-ray diffraction, and Raman-scattering studies in polycrystalline (La 1Ϫy Nd y) 1Ϫx Ca x MnO 3 (yϭ0.0,0.5,1.0, and xϭ1/3) samples are presented. The samples with yϭ0.5 and 1.0 show complex magnetic states at low temperatures, with a ferromagnetic coupling strength that weakens with increasing y. X-ray measurements show a single crystallographic phase at all temperatures for yϭ0.5, with lattice parameter anomalies at temperatures related to electronic and magnetic transitions. The presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…Similar changes are also seen in the Raman scattering. 61 Overall, however, the changes in the phonon density-of-states are modest.…”
mentioning
confidence: 99%
“…Similar changes are also seen in the Raman scattering. 61 Overall, however, the changes in the phonon density-of-states are modest.…”
mentioning
confidence: 99%
“…This kind of FiM structure is bolstered by the molecular field model for Gd 0.67 Ca 0.33 MnO 3 [13]. The existence of AFM component in such compounds has been also proved by the lack of saturation in the macroscopic magnetization data of Nd-based single crystals [14][15][16]. The specific heat of NSMO shows abnormal features that are interpreted in terms of an Nd-Mn exchange interaction that couples the orderings of the two spin systems [17].…”
Section: Introductionmentioning
confidence: 90%
“…Earlier work indicated that lower values of average cationic radius of rare-earth site /r A S would suppress the double exchange and then increase the MR ratio [7]. Recently, abnormal phenomena accompanying with REdoping in such compounds have been reported [8][9][10][11][12][13][14][15][16][17][18]. Nd 2/3 Sr 1/ 3 MnO 3 (NSMO) exhibits an abnormal electric resistivity behavior such as Kondo-like effect at low temperature [8].…”
Section: Introductionmentioning
confidence: 99%
“…Можно сделать вывод, что намагниченность в этой области тем-ператур вызвана только ориентацией магнитных момен-тов суперпарамагнитных кластеров магнитным полем. Следует отметить, что в более ранних работах [16][17][18][19][20] по изучению неодимовых манганитов отмечалось, что в магнитном поле несколько Тесла насыщения на кривых намагниченности не было достигнуто, что вызвано скошенным или ФИМ упорядочением моментов ионов Nd и Mn. В то же время изучение диффракции нейтронов неодимовых манганитов показало, что под-решетки Nd и Mn имеют тенденцию упорядочиваться ферромагнитно [21].…”
Section: результаты и их обсуждениеunclassified